2006
DOI: 10.1103/physrevd.73.096002
|View full text |Cite
|
Sign up to set email alerts
|

Neutrino mass through concomitant breakdown of the U(1) chiral and scale symmetries

Abstract: The possibility of generating neutrino mass through see-saw mechanism involving U(1) chiral Peccei-Quinn and scale symmetries breakdown is discussed. We consider a generic scale invariant model which has three Majorana fermions and a complex scalar singlet, which might be the one responsible for an invisible axion, and we perform a summation of all leading logarithmic radiative corrections to the tree level potential. The effective potential so obtained is stable and drives the scalar field to a nonzero vacuum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Substituting the expansion (4) in (8) we find, at the leading order (terms proportional to n L nÀ2 ), À @ @L þ ð2Þ @ @ S LL eff ðÞ ¼ 0:…”
Section: General Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Substituting the expansion (4) in (8) we find, at the leading order (terms proportional to n L nÀ2 ), À @ @L þ ð2Þ @ @ S LL eff ðÞ ¼ 0:…”
Section: General Considerationsmentioning
confidence: 99%
“…An important example where the RGE have dramatically improved the information obtained in the loop approximation is in the analysis of the effective potential for the standard model with conformal invariance: from the standard one-loop approximation, the effective action of the model does not seems to be stable, but with the more precise approximation obtained using the RGE, one discovers it actually is [4]. For other examples see [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Up to v/v S corrections, at low scale the model is just the ν2HDM discussed in Ref [9]. with a very weakly coupled axion 6. For reviews of the strong CP problem and axions see e.g.Refs [17][18][19][20][21]…”
mentioning
confidence: 99%
“…At the same time, the required extension of the scalar sector improves on the stability of the SM vacuum. We do not require additional fermions (recent proposals that include righthanded neutrinos in connection with an invisible axion were presented in [50][51][52][53][54][55], while an extensive list of studies on the subject is found in [1]).…”
Section: Discussionmentioning
confidence: 99%